LABOR PROTECTION AND ITS IMPORTANCE FOR THE GENERATION OF BIOFUELS - Dias, Fernando Ramos Bernardes; Borges , Alexandre Walmott (Seven Editora, 2024)
This article studies the importance of Labor Law from the point of view of fundamental social rights, and how important it is for an adequate environmental policy and the energy matrix of biofuels. The national sustainable energy matrix is dependent on agricultural work, and this must be fair and adequate for energy generation to be truly sustainable. The research has the nature of strategic basic research presenting a possible solution in the regulation of work in the field. As it seeks to describe the labor regulatory system, but also to present a regulatory solution, it has a descriptive and exploratory character. The approach to the work is qualitative, seeking to express, in the end, the positive valuation for the correct respect for labor legislation and how important this is for the generation of clean energy. The research relied on bibliographic and documentary sources for its final draft. DOI:https://doi.org/10.56238/sevened2024.029-054